SIMULASI PERGERAKAN RUNTUHAN LONGSOR MENGGUNAKAN MODEL SAVAGE-HUTTER DENGAN FINITE VOLUME METHOD - LUDICA, ALIFANDA PINKAN; GUNAWAN, P. H.; ROHMAWATI, ANIQ A. (E-Jurnal Matematika, 2018)
The avalanche is simulated using the Savage-Hutter model with Finite Volume Method (FVM) as a numerical solution in one dimension. The scheme used in FVM is collocated-grid. The aim of this research is to observe the avalanche based on different sediment types on the incline bed with the same initial sediment height. These simulations produce the value of velocity and height avalanche. For each type of sediment has a difference in velocity and height of avalanche affected by the internal angle of friction and the bed friction angle. Sediments with the highest bed friction angle have highest speed. The average velocity of each sediment are Quartz with u = 10.627, Yellow Sand with u = 7.437, and Rice with u = 2.1178 at time t = 1.